2014
DOI: 10.1002/mds.25994
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability of PINK1 expression: 12 Years' clinical follow-up of two Italian families

Abstract: We expanded the phenotypic profile of PINK1-related parkinsonism, including psychiatric and cognitive features as part of clinical presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…This means that, in our experimental model, HET individuals were expected to be less cognitively impaired than HOM patients. However, consistent with a previous study on PINK1 mutation carriers (including part of the patients enrolled here) [12], all but one subjects from either group (HET, HOM) reported pathological scores at MoCA. Moreover, the two cognitively preserved individuals were both PINK1 heterozygous carriers, while all Park2 mutation carriers (3 HET, 2 HOM) showed pathological scores at MoCA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This means that, in our experimental model, HET individuals were expected to be less cognitively impaired than HOM patients. However, consistent with a previous study on PINK1 mutation carriers (including part of the patients enrolled here) [12], all but one subjects from either group (HET, HOM) reported pathological scores at MoCA. Moreover, the two cognitively preserved individuals were both PINK1 heterozygous carriers, while all Park2 mutation carriers (3 HET, 2 HOM) showed pathological scores at MoCA.…”
Section: Discussionsupporting
confidence: 91%
“…In the HET group, two PINK1 carriers received a diagnosis of possible PD (subjects F1-IV:13/M and F1-IV:12/M, already reported in a previous publication) [12]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful analysis of families with mutations in recessive Parkinson’s disease genes revealed that heterozygous mutation carriers may also develop mild parkinsonism (Criscuolo et al , 2006; Klein et al , 2007; Eggers et al , 2010; Ricciardi et al , 2014). In a few instances, a seemingly autosomal dominant mode of inheritance was found in heterozygous carriers of mutations in recessive Parkinson’s disease genes (Klein et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction likely plays a central role in this process, although its underlying mechanisms are poorly understood (Haddad and Nakamura, 2015). Mutations in PTEN-induced putative kinase 1 (PINK1) cause rare inherited forms of PD (Valente et al, 2004; Ricciardi et al, 2014), providing the first direct genetic evidence that mitochondrial dysfunction can cause PD. Heterozygous mutations in PINK1 are also a risk factor for sporadic PD (Puschmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%